Which market integration measure? - Monica Billio; Michael Donadelli; Antonio Paradiso; Max Riedel (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
This paper compares the dynamics of the financial integration process as described by different empirical approaches. To this end, a wide range of measures accounting for several dimensions of integration is employed. In addition, we evaluate the performance of each measure by relying on an established international finance result, i.e., increasing financial integration leads to declining international portfolio diversification benefits. Using monthly equity market data for three different country groups (i.e., developed markets, emerging markets, developed plus emerging markets) and a dynamic indicator of international portfolio diversification benefits, we find that (i) all measures give rise to a very similar long-run integration pattern; (ii) the standard correlation explains variations in diversification benefits as well or better than more sophisticated measures. These Findings are robust to a battery of robustness checks.
Keywords: F15; F44; G15; 330; equity market integration; dynamic correlation; principal components; international diversification benefits